Prognostic value of interleukin-34 and interleukin-38 in patients with newly diagnosed atrial fibrillation - Ma, Jiaxue; Wu, Na; Yuan, Zhiquan; Chen, Yanxiu; Li, Chengying; Xie, Weijia; Zhang, Zhihui; Li, Yafei; Zhong, Li (Frontiers in Cardiovascular Medicine, 2023)
Interleukin (IL)-34 and IL-38 are associated with cardiovascular disease (CVD), however, their involvement in atrial fibrillation (AF) and associated adverse events remains uncertain. Therefore, we aim to investigate their association with different prognostic factors of AF through a prospective cohort study and assess their predictive value. The patients with new-onset non-valvular AF were enrolled in the Department of Cardiovascular Medicine of the Southwest Hospital of the Army Medical University (Third Military Medical University) in Chongqing, China. The baseline levels of plasma IL-34, IL38, NT-proBNP, hs-cTnT, and GDF-15 were measured and their correlation with AF-related adverse events were analyzed in a Cox proportional-hazards regression model. The C-statistic, NRI, and IDI were used to evaluate the performance of the AF prognostic model. DCA was used to assess the clinical net benefit of the original and modified models. 299 patients with new-onset AF were enrolled. Results from Cox regression analyses indicated that the higher concentration of IL-34 was associated with a lower risk of stroke (hazard ratio [HR]: 0.36, 95% confidence interval [CI] 0.17-0.78, P=0.010) and the higher level of IL-38 was associated with an increased risk of all-cause death (HR: 3.11, 95%CI 1.16-8.29, P=0.024). In addition, elevated hs-cTnT and NT-proBNP levels were associated with a higher risk of stroke (HR: 3.09, 95%CI 1.33-7.19, P=0.009) and all-cause mortality (HR: 2.77, 95%CI 1.13-6.78, P=0.025), respectively. According to the assessment of the risk model of all-cause death associated with AF, the C-statistic of the modified CHA2DS2-VASc combined with IL-38 and NT-proBNP increased by 0.10 compared with the original score (P=0.005) and had significant statistical differences in reclassification (IDI: 3.7% [95%CI 1.1%-13.3%], P<0.001; NRI: 77.6% [95%CI 21.9%-82.7%], P<0.001). There were no statistically significant differences in discrimination power between the ABC score and the best model. Our results suggest that IL-34 and IL-38 are independently associated with stroke and all-cause mortality in patients with AF, respectively. Moreover, adding IL-38 and NT-proBNP to the CHA2DS2-VASc score significantly improved the predictive ability of AF-related all-cause death. Finally, the performance of the new score in predicting AF prognosis is comparable to that of the ABC score.